PROBLEMATIKA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Rudi Haryadi; Fitria Selviani (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of this research is to find out the problems of online learning during the Covid-19 pandemic. This research method uses literature study or library research by taking reading sources from secondary data collected through textbooks, scientific journals, e-books and other sources relevant to the research problem. This type of research was analyzed qualitatively with an interactive model consisting of data collection, data reduction, drawing conclusions and verification. The results of this study indicate that online learning is one solution so that the learning process continues during the Covid-19 pandemic. But in this learning there are various problems experienced by various parties, namely educational institutions, educators (teachers and lecturers), students and parents of students. The problems that exist in educational institutions are the lack of availability of telecommunication technology infrastructure, multimedia, information and platforms that support the process of teaching and learning activities online, from educators in the form of limitations in the use of IT, as well as the difficulty of forming student personality characteristics and applying learning media so that students can understand the material presented, from students, namely most students are not familiar with online learning and due to limited internet facilities, from parents the lack of time available to accompany their children during online learning because not all parents can divide their time between work and mentoring children in House.